LARYNGEAL DYSPLASIA, UP TO DATE - Boričić, Novica (Medicinski podmladak, 2022)
Laryngeal dysplasia is a precancerous lesion of the laryngeal epithelium. Cigarette smoking and alcohol consumption have been identified as the two most important etiological risk factors for the development of laryngeal dysplasia. It is considered that low-grade dysplasias have a lower malignant potential and that high-grade dysplasias have a higher potential for transformation into squamous cell carcinoma. It is necessary to establish a precise diagnosis to prevent the transformation of dysplasia into squamous cell carcinoma. Dysplasia has a diverse macroscopic presentation including leukoplakia, erythroleukoplakia, hyperkeratotic thickening, or exophytic tumor-like masses. Available laryngoscopic techniques are not diagnostically efficient. The diagnosis is based on the histopathological picture of the lesion. There are several classification systems of laryngeal dysplasias that are used in practice, but each relies on the subjective interpretation of morphological criteria. There is great interobserver variability among pathologists for each of the existing dysplasia classifications. All classification systems have weak correlations between the degree of dysplasia and the risk of malignant transformation. So far, there is no specific biological or genetic marker specific for dysplasia or type of laryngeal dysplasia, but recent studies identified some biomarkers that could be used to determine the malignant potential of dysplasias. The aim of this mini-review is to show the novelties in the classification, etiology, histopathological diagnosis, and therapy of laryngeal dysplasia.